CONTESTING THE ASIAN FEMALE IDENTITY THROUGH TRANSCULTURALISM IN RICE WITHOUT RAIN - Syamsina Zahurin Binti Shamsuddin; Ida Baizura Bahar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Rice without Rain (1986), written by the Chinese American writer, Minfong Ho (b. 1951), has been recognised internationally and awarded with numerous awards including Best Books for Young Adults (1991). Set in Thailand, the text is believed to have been overlooked in regards to works by Ho as scholarships on the issue of the Asian female identity through the lens of transculturalism are scarce. Previous scholarship on Rice without Rain, for example, focused more on the general identity of the female characters through the concepts of a “whole” self and female “space” for Thai and American-born Thai young women (Thongthiraj, 2006). We hypothesise here, however, that the true identity of the Asian female is reflected through the depiction of Jinda in Rice without Rain which is believed to contain the concepts of transculture/ality and identity fluidity. Here, we explore the concept of transculture/ality by the transcultural scholar, Arianna Dagnino (2015), as a platform to contest the current understanding of the Asian female identity by the scholar of English and Comparative Literature, Lalaine Yanilla Aquino (2011) who states that the Asian female identity is recognized culturally as powerless, voiceless and submissive. We examine how transculturalism forms the identity of the protagonist using the concept of transculture/ality by Dagnino and identity fluidity by the cultural theorist Stuart Hall (2011). Findings of this paper demonstrate the application of transculture/ality and identity fluidity in a work of literature revealing that Jinda contests the stereotypical understanding of the Asian Female identity reflecting transculture/ality and identity fluidity.